Prophylactic vaccination targeting ERBB3 decreases polyp burden in a mouse model of human colorectal cancer. (2nd January 2017) - Bautz, David J.; Sherpa, Ang T.; Threadgill, David W.
ABSTRACT: Prophylactic vaccination is typically utilized for the prevention of communicable diseases such as measles and influenza but, with the exception of vaccines to prevent cervical cancer, is not widely used as a means of preventing or reducing the incidence of cancer. Here, we utilize a peptide-based immunotherapeutic approach targeting ERBB3, a pseudo-kinase member of the EGFR/ERBB family of receptor tyrosine kinases, as a means of preventing occurrence of colon polyps. Administration of the peptide resulted in a significant decrease in the development of intestinal polyps in C57BL/6J- Apc Min mice, a model of familial adenomatous polyposis (FAP). In addition, even though they were not vaccinated, Apc Min offspring born to vaccinated females developed significantly fewer polyps than offspring born to control females. Lastly, to validate ERBB as a valid target for vaccination, we found no overt toxicity, increases in apoptosis, or morphological changes in tissues where Erbb3 was ablated in adult mice. These results indicate that prophylactic vaccination targeting ERBB3 could prevent the development of colon polyps in an at-risk patient population.